Mendelian non-syndromic obesity - Paolacci, Stefano; Pompucci, Giuseppe; Paolini, Barbara; Del Ciondolo, Irene; Miggiano, Giacinto Abele Donato; Aquilanti, Barbara; Scaramuzza, Andrea; Velluti, Valeria; Matera, Giuseppina; Gagliardi, Lucilla; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Obesity is highly heritable and arises from the interplay of many genes and environmental factors. It can be defined as the result of prolonged imbalance between calorie intake and energy utilization. About 5% of cases of non-syndromic obesity are monogenic (Mendelian obesity). The amount of adipose tissue in the body is mainly regulated by leptin, a hormone produced by adipocytes, and Mendelian obesity is mainly caused by mutations that disrupt the leptin/melanocortin pathway. In this article, we summarize the genes involved in genetic obesity and the test we use for genetic analysis.